Digital Fame, Ecological Fragility: Strategic Management of Trend-Driven Volcanic Tourism - Astrid Apriliana; Haniek Listyorini (Journal of Tourism Sustainability, 2026)
Social media-induced tourism triggers rapid visitor surges that often outpace destination management capacity. This study examines Kalitalang Ecotourism on Mount Merapi's slopes, where "viral hiking" and FOMO-driven trends caused a 130% annual increase in arrivals. Using a mixed-method approach, the research identifies strategic factors through IFAS and EFAS matrices. Data reveals a strong position in Quadrant I with an IFAS score of 3.81 and an EFAS score of 4.10. Despite high growth potential, the findings highlight severe risks of exceeding carrying capacity and ecological degradation. Sustainable development requires shifting from traditional promotion to strict digital gatekeeping and waste management. This research offers a trend-sensitive framework to protect volcanic destinations from the volatility of digital popularity.